The watcher in the woods [videorecording (DVD)] - Davis, Bette, 1908-1989; Baker, Carroll, 1931-; McCallum, David, 1933-; Johnson, Lynn-Holly; Randall, Florence Engel, 1917- (Disney DVD., 2004)
When an American family moves into a remote English house in the woods, the two daughters begin to see a young girl who vanished in the woods during a solar eclipse 20 years ago. Is it a ghost, or something more?